UJI DAYA ANTIMIKROBA EKSTRAK ETANOL DAUN SIRIH MERAH (Piper Crocatum Ruiz & Pav.) TERHADAP PERTUMBUHAN Staphylococcus aureus ATCC 6538, Eschericia coli ATCC 11229 DAN Candida albicans ATCC 10231 SECARA IN VITRO - Anika Candrasari; M. Amin Romas; Ovi Rizky Astuti (Biomedika, 2012)
Red betel leaf contains flavonoids, alkaloids and essential oils that are suspected able to inhibit the growth of microbes. This study aims to analyze antimicrobial activity of ethanol extract of red betel leaf agains to Staphylococcus aureus, Eschericia coli and Candida albicans. Subjects were red betel leaf ethanol extract at concentration of 2.5%, 5%, 10%, 20%, 40%, 80% and 100%. As a positive control used amoxycilin, chloramphenicol and ketoconazole. The study showed that concentration 10 % - 100 % inhibit the growth of Staphylococcus aureus. In Escherichia coli all the data obtained, having an average which is not much different from the mean of the negative control. While on Candida albicans average diameter of inhibition zone of extract concentration 40% p = 0.197 concluded that statistically has significant antifungal power compared with ketokonazole.Keywords: Ethanol extract, Piper Ruiz Pav crocatum, Antimicrobial, Staphylococcus aureus, Escherichia coli, Candida albican